Making Digital Content of Arab National Libraries Accessible Through Social Media: An Analytical Study (Damascus University Journal of arts and humanities sciences, 2026)
Libraries in all their forms and types seek to enhance their knowledge and scientific expertise for users. In light of the widespread proliferation of social media networks, which offer vast opportunities for libraries to provide a diverse array of services-particularly in making digital content accessible-this study aims to clarify the concept of digital content, its importance, and its characteristics. The focus is on the accessibility of Arab national libraries through social media networks, using a descriptive-analytical approach as the most suitable method for presenting and discussing information accuratelyand scientifically. The study reached the following conclusions: The results revealed that the Arab national libraries possess accounts on various social networking sites. Among these, the King Fahd National Library excels in providing digital content across all its social media platforms. The study recommends raising awareness among information specialists about the importance of disseminating digital content through social media and calls for organizing training courses on managing digital content via these platforms.
Keywords: Digital Content; Arab National Libraries; Social Media Networks; Arab World